Rosacea: do microbes have some role in its causation? A cross-sectional study from North-East India - Devi, Bijayanti; Bhaumik, Jantu Kumar; Bhattacharjee, Nandita (International Journal of Research in Dermatology, 2019)
Background: Rosacea is a common inflammatory disease affecting the centrofacial skin. The etiopathogenesis is unknown and the disease follows a chronic course. It causes great social discomfort and reduces quality of life. Methods: A cross sectional study was conducted from October 2011 to September 2013 in the Department of Dermatology, Venereology and Leprology of Regional Institute of Medical Sciences in Imphal, Manipur and all the patients diagnosed with rosacea were included. A detailed history and clinical examination were done and recorded in a preset proforma. Potassium hydroxide mount of skin scrapings and Gram stain as well as culture from lesion and control were performed. Results: A total of 72 patients were included with female predominance. The mean age of the patients was 31.64±9.623 years. Sun exposure (70.8%) was the commonest exacerbating factor followed by fried spicy food (69.4%). Persistent erythema was seen in most of the patients (97.2%) and ETR was the commonest subtype (65.3%). Associated ocular manifestations were present in 4.2% of patients. The prevalence of Demodex mite was found to be higher in lesional skin as compared to the control. Culture from both lesion and control showed predominant growth of coagulase-negative staphylococcus (87% and 78.3% respectively). Conclusions: Rosacea is a multifactorial disorder with diverse clinical spectrum. Elimination of the triggering factors may help in controlling the flares and improve the quality of life.